Możliwości aktywizacji osób zmarginalizowanych na rynku pracy - ocena efektywności działań na przykładzie miasta do 20 tys. mieszkańców - Książkiewicz, Izabela (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2010)
This case study, developed by the author, describes the case of three municipalities of North Masovia: Pszasnysz, Chorzele i Myszyniec, whose Municipal Social Assistance Centres were conducting projects within the framework of the Human Capital Programme. According to the document National Strategic Frameworks of Reference (National Strategy of Cohesiveness,) all European Social Fund resources in Poland during the years 2007 – 2013 (9.7 billion Euro) were used for tasks as part of the Human Capital Programme. Th e Human Capital Programme aims primarily to increase of employment and social cohesion. Several sub-targets are derived from this main goal: 1. Increasing the level of work activity and employment capabilities of the unemployed and jozbpassive; 2. Decreasing areas of social exclusion; 3. Improving employees’ and firms’ capabilities to adapt to a changing economy; 4. Improving the cohesion of society’s education on every level of learning by simultaneously increasing the quality of educational services and linking them more strongly to a knowledge -based economy; 5. Increasing public service’s potential within the range of developing polices, providing high quality services and strengthening mechanisms of partnership 6. Increasing of territorial integrity. Th is case study seeks to answer the question: How many of the local government’s implementations using European Union funds fulfil the Human Capital Programme’s assumptions? Th e study of these three municipalities provides a basis for further studies in which I will conduct a more detailed analysis of implemented programs’ efficiency and their impact on communities’ social and economic development.